Assistência técnica e extensão rural para cooperativas de agricultura familiar: um estudo sobre as bases conceituais e orientações para a ação extensionista - Gregolin, Marcos Roberto Pires (2021)
This research contextualizes the Technical Assistance and Rural Extension (ATER), mainly understanding that since the enactment of the Brazilian Law number 12,188 in 2010, the management and commercialization processes made by family farmers are included in the hall of services offered by this legislation. The “Mais Gestão” Project was created officially in 2012, based in the National Policy for Technical Assistance and Rural Extension (PNATER) and was characterized as an innovative project because it wasn’t encompassed the family farmers directly in the extensions activities, but the economic organizations composed by them, which operates to the transformation and commercialization of their products. Organized by the Agrarian Development Ministry (MDA) in Brazil, the project aims to identify and solve weaknesses in technical, managerial, and technological areas. Also, through the resolutions, increment the competitiveness and promote a sustainable culture in the benefited organizations. Due the project consonance with PNATER since the begun, both have their principles linked, emphasizing here the participative methodologies adoption as a standard in its normative documents. To choose the benefited organizations in the project, it was considered two criteria: to have a significative number of family farmers as members (what is guarantee by a document called DAP jurídica) and have commercialization of products to governmental markets (like the programs PAA and PNAE). This Thesis aimed to analyses the methodological and rational binding of “Mais Gestão” and the specificities of family farmers cooperatives benefited by the extension activities. The methodology can be categorized as bibliographic and documental, being the results described in four articles linked with the Thesis specific objectives. The first article was elaborated with the aim of contextualize the history of cooperativism in Brazil, focusing on a dualism of representation. It was demonstrated that within the scope of agricultural cooperativism, a dualism was established, being the cooperatives of family farmers and of solidarity economy an alternative to the traditional cooperatives, which over time had not represent the food production system, but the commodity ones, created by the agricultural modernization. In the second and third articles, it was aimed to compare the practices guided by “Mais Gestão” project with the current methodological premises of ATER. To this, it was presented arguments that shows the efforts supported by the managers of the public policy to adapt the project to the family farmers reality. However, it was possible to identify that these efforts have practical and operational elements that aren’t ideals, according to the participative methodologies, knowledge exchange, dialogical processes, and knowledge construction. Lastly, in the fourth article, the aim was to compare the practices guided by “Mais Gestão” project now with the typical-ideals characteristics of rationalities of organizational processes and dynamics. Considering this theme, it was discussed the problem that, for several authors, family farmer cooperatives (considered as alternatives of resistance, or as representatives of the “new cooperativism”) are guided by rational actions in relation to values and not only by actions rationally linked to ends, as is customary in mercantile capitalist environments. From this, it was presented contributions from national and international literature that address these different rational actions in organizations, through which it was possible to build a framework with organizational processes and dimensions, in addition to typical-ideal characteristics of rational actions (instrumental/formal or substantive/collectivist) for each of the processes or dimensions. Based on the analysis of the methodological guide of the “Mais Gestão” project (through the focus of rationalities) and understanding that family farmer cooperatives are characterized as organizations guided by substantive rationality, denying the supremacy of bureaucracy, as well as the preposition of the economic to the social, it was concluded that there is a gap between the proposed methodology and the characteristics of family farmer cooperatives, beneficiaries of extension activities.